FARAIDH AND ITS CORRELATION WITH MATHEMATICS CONCEPTS IN LIFE - Putri, Farah Rahmatika; Muna, Faizul; Nurhuda, Abid (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2023)
Faraidh is one of the sciences that every Muslim must know. This is evidenced by the existence of arguments regarding this knowledge in the Qur'an. Meanwhile, in the division and calculations, another science tool is needed, namely mathematics as a companion. So the purpose of this study is to describe Faraidh and its correlation with mathematical concepts in life. The method used is descriptive qualitative with a literature study approach, then the data collection uses documentation techniques and is analyzed and finally concluded. The results of the study show that Faraidh Science has a very close relationship with Mathematical Concepts so that it produces fractions consisting for commonly known as alfurudhul muqoddaroh for each heir.